High-Ni cathode material improved with Zr for stable cycling of Li-ion rechargeable batteries. Issue 45 (17th July 2020) - Park, Kwangjin; Ham, Dong Jin; Park, Seong Yong; Jang, Jihyun; Yeon, Dong-Hee; Moon, San; Ahn, Sung Jin
Abstract : The Zr solvent solution method, which allows primary and secondary particles of LiNi0.90 Co0.05 Mn0.05 O2 (NCM) to be uniformly doped with Zr and simultaneously to be coated with an Li2 ZrO3 layer, is introduced in this paper. Abstract : The Zr solvent solution method, which allows primary and secondary particles of LiNi0.90 Co0.05 Mn0.05 O2 (NCM) to be uniformly doped with Zr and simultaneously to be coated with an Li2 ZrO3 layer, is introduced in this paper. For Zr doped NCM, which is formed using the Zr solvent solution method (L-NCM), most of the pinholes inside the precursor disappear owing to the diffusion of the Zr dopant solution compared with Zr-doped NCM, which is formed using the dry solid mixing method from the (Ni0.90 Co0.05 Mn0.05 )(OH)2 precursor and the Zr source (S-NCM), and Li2 ZrO3 is formed at the pinhole sites. The mechanical strength of the powder is enhanced by the removal of the pinholes by the formation of Li2 ZrO3 resulting from diffusion of the solvent during the mixing process, which provides protection from cracking. The coating layer functions as a protective layer during the washing process for removing the residual Li. The electrochemical performance is improved by the synergetic effects of suitable coatings and the enhanced structural stability. The capacity-retentions for 2032 coin cells are 86.08%, 92.12%, and 96.85% at the 50 th cycle for pristine NCM, S-NCM, and L-NCM, respectively. The superiority of the liquid mixing method is demonstrated for 18 650 full cells. In the 300 th cycle in the voltage range of 2.8–4.35 V, the capacity-retentions for S-NCM and L-NCM are 77.72% and 81.95%, respectively.